Implementation of personal data protection based on dignity justice - Japansen Sinaga; Rolib Sitorus; Joy Zaman Felix Saragih (Priviet Social Sciences Journal, 2025)
This study analyzes the implementation of personal data protection in Indonesia, focusing on the concept of dignified justice. This is motivated by the rampant incidents of personal data breaches that cause material and immaterial losses and question the extent to which the existing legal framework can guarantee individual rights fairly and with dignity. The main objective of this study is to evaluate the effectiveness of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) in realizing dignified justice and to identify challenges and opportunities in its implementation. This study uses a normative legal research method with a statutory and conceptual approach to analyze regulations, legal doctrines, and related case studies. The main findings indicate that although the PDP Law has been a significant step forward, there are still gaps in its implementation, especially regarding mechanisms for restoring victims’ rights, the transparency of data processing, and the accountability of data controllers, which have not fully reflected the principle of dignified justice. The implementation of personal data protection is often hampered by the public’s low digital literacy and the suboptimal capacity of law enforcement. Ultimately, to achieve personal data protection based on dignified justice, compliance with regulations and strengthening human rights values in every aspect of data handling, from collection to dispute resolution, by prioritizing individual dignity, are required.